Młodzież jako przedmiot zainteresowania socjologii = The youth as a subject of interest in sociology - Niezgoda, Marian (1943- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper attempts to answer the following question: Are sociology and sociologists interested in the youth? The question seems to be as trivial as the predicted answer - certainly yes. The existence of such a sociological subfield as sociology of youth and considerable literature resulting from general (theoretical) reflection and numerous studies may justify the answer.
Keywords: sociology of youth; youth; generations; socjologia młodzieży; młodzież; generacja